Teacher's Practice Regarding Cardiopulmonary Resuscitation at Basic Schools in Erbil City - Jawdat Mamand Akhagbaker; Kareem Fattah Aziz (Hawler Medical University, 2024)
Background and objectives: Every day, either by accident or illness, there are numerous situations in which the safety of individuals, families or communities is endangered. >2000 children worldwide die every day as a result of unintentional injuries. The majority of risks influencing a cardiac arrest in a school are related to physical activity, such as participating in sports or having an airway obstruction or trauma event. In the United States and Europe, one million people experience cardiac arrests annually. The aim of this study was to assess the basic school teachers' practices regarding cardiopulmonary resuscitation at basic schools in Erbil City. Methods: A cross-sectional study was carried out. To assess the practices of basic school teachers regarding cardiopulmonary resuscitation. The study was conducted from January 20, 2021 to May 15, 2022. This study was conducted in basic schools in Erbil city according to six municipalities. The sample size was 470 teachers. The observational checklist technique was used to assess cardiopulmonary resuscitation performance. Results: The majority of them were female (74%), more than half of them have a diploma (52.3%), the majority of age group were between 37-48 years old which represents 51%, the mean age was (43.85±8.27), most of the teachers were married (86.4%), the majority of them did not a training course (86.4%). Several teachers use tradition at media (9.6%) and social media (44.7). A lot of barriers were faced teachers to prevent participation in training courses were not found in professional training course The majority of the schoolteachers had poor levels of practice (51.1%) regarding the performance of cardiopulmonary resuscitation. Conclusion: The majority of schoolteachers had poor levels of practice regarding cardio-pulmonary resuscitation. There was a significant association between the performance of CPR and some socio-demographic variables like age group, gender, years of experience, and desire to attend CPR training course.